[Ending a winter's war ; Miracle in Central Visayas ; The vanishing wildlife [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Satur Ocampo, a communist leader interviewed by Probe Team about prospects for peace for government survival. Farmers of Central Visayas telling how they won the war against deforestation and the fishermen in their fight against illegal fishing. A tour at the Crocodile Farm Institute in Puerto Princesa, Palawan. Probe interviews management on how to take care of those endangered species.
Ending a writer's war (15 min.) -- Miracle in Central Visayas (15 min.) -- The vanishing wildlife (9 min.)
VHS.
Keywords: Crocodile Farm Institute (Palawan); Peace negotiations -- Philippines; Conflict management -- Philippines; Crocodiles -- Philippines -- Palawan; Central Visayas -- Economic conditions, 1992.